2D time‐domain full‐waveform inversion of SH‐ and Love‐waves for geotechnical site characterization. Issue 3 (22nd December 2020) - Chen, Ruoyu; Tran, Khiem T.; Wang, Yao
ABSTRACT: Full‐waveform inversion has proved to be an effective and robust approach for near‐surface site characterization. Past full‐waveform inversion studies have mostly focused on Rayleigh wave, with only a few studies focussing on SH‐ and Love‐waves. Compared with Rayleigh waves, the main advantages of using SH‐ and Love‐waves are that they are more sensitive to mass density of materials and require much less computing time for simulation. In this study, we present an efficient SH‐ and Love‐wave full‐waveform inversion method to extract both S‐wave velocity and mass density of soil and rock. The method is based on the solution of 2D elastic SH‐wave equations and the adjoint‐state gradient approach with an implementation of Tikhonov regularization. We use synthetic and field experiments to test the capability of the method. The synthetic experiment indicates that the presented method can accurately characterize a challenging soil profiel represented by the presence of a velocity reversal along with variable layers of high and low S‐wave velocity and density. Variable layer interfaces, true S‐wave velocity and density values are well recovered. The field experiment successfully characterizes the subsurface structure to a depth of 18 m, that includes a soil layer underlain by limestone bedrock. Two invasive standard penetration tests were conducted to verify the inverted seismic results. The trend in depth of the standard penetration test N‐values generally agrees with the inverted results, including identification of a soft soil layer.